Modelagem de Poliedros de Arquimedes Via Cinema 4D - Ramos, João Barbosa (2024)
Cinema 4D is 3D creation software that encludes modeling, animation, texturing, and rendering of objects. The objective is to provide a brief introduction to 3D modeling with Cinema 4D and to utilize this tool for modeling Archimedean Polyhedra. These polyhedra belong to a special class of convex three-dimensional solids, named after the Greek mathematician Archimedes. The faces of these polyhedra consist of regular polygons of more than one type, and there are only thirteen of them. To model these polyhedra, it is first necessary to conduct a study on their geometric properties and construction methods based on other regular polyhedra, and then adapt these measurements to the software tools. Cinema 4D offers a versatile and flexible approach to exploring interesting geometric mathematical shapes with its advanced polygonal modeling tools.